2019
DOI: 10.25177/jfst.4.4.ra.479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioactive compounds of defatted flaxseed meal on rheological and sensorial properties of toast and cake

Abstract: This study was conducted to investigate the chemical composition and the storage stability of flaxseeds defatted meal fractions as food ingredients, phenolic contents and antioxidant activity of flaxseed meal extracts. Effect of substitution of wheat flour with different concentrations of defatted flaxseeds meal on rheological and sensory properties of toast bread, and cake was also investigated. The results indicated that flaxseed defatted meal is rich in protein, fiber and minerals and poor in its carbohydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…This is due to the increased content of protein (20.5%) and fiber (4.36%) in flaxseed flour compared to WF100. Our results agreed with Xu et al, (2014) and Mostafa et al, (2019) who confirmed that the mixture of wheat flour and flaxseed flour leads to an increase in dough absorption of water compared to the control sample. According to the current findings, samples supplemented with CHF absorbed water slightly more readily than wheat flour.…”
Section: -Water Absorptionsupporting
confidence: 93%
“…This is due to the increased content of protein (20.5%) and fiber (4.36%) in flaxseed flour compared to WF100. Our results agreed with Xu et al, (2014) and Mostafa et al, (2019) who confirmed that the mixture of wheat flour and flaxseed flour leads to an increase in dough absorption of water compared to the control sample. According to the current findings, samples supplemented with CHF absorbed water slightly more readily than wheat flour.…”
Section: -Water Absorptionsupporting
confidence: 93%
“…Consuming flaxseeds only for our diets is a somewhat monotonous activity, and some people find flaxseed's weak sensory appeal offensive. Thus, whole or milled flaxseed has been incorporated into a variety of common foods, such as breads, crackers, muffins, energy bars, snacks, cookies, cake and soups (Karakurt et al, 2022;Sanmartin et al, 2020;Lohan et al, 2020;Mostafa et al, 2019). Flaxseed may have several positive effects on health, including reducing blood fat, antiinflammation, preventing cancer, and aiding weight loss, because it contains bioactive including protein, dietary fiber, and lignan (Bechlin et al, 2019;de Oliveira Giarola et al, 2019;Lan et al, 2020), for healthy foods needs from customers, researchers and food producers are working to develop products based on flaxseeds.…”
Section: Introductionmentioning
confidence: 99%